Saying the Impossible, Imagining Change. Bronislaw Baczko and the History of «Utopian Discourse» - Luca Scuccimarra (Scienza & Politica)
It is enough to skim the very first pages of the volume Lumières de l’Utopie to touch upon the connections, profound even if not completely explicit, that link Bronislaw Baczko’s historiography to that great process of methodological renewal of historical studies that today we are accustomed to call the «linguistic turn». This paper aims precisely at delving into this specific aspect of the Polish historian’s work, dwelling in particular on the contribution that his view of the history of modern “utopian discourse” offered to a deeper and more conscious understanding of the conflicting events of European modernization.